Capacity Development of Village-Owned Enterprises in Increasing the Success of the Poverty Vulnerability Reduction Program (PK2) - Eka Alfajri Oktaviani; Isnaini Rodiyah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to find out about the capacity development of BUMDes in increasing the success of the PK2 Jalin Matra program in Semambung Village, Jabon District, Sidoarjo Regency. The research method used descriptive qualitative method using purposive sampling technique in determining the informants, namely the Village Head, BUMDes management and the community. Data collection techniques were through interviews, observation and documentation. The data analysis technique uses an interactive analysis model consisting of data collection, data reduction, data presentation and drawing conclusions. The results of this study show that according to Soeprapto's theory of capacity development, there are 2 levels, namely the organizational and individual levels. Organizational level, organizational structure is clear and there are SOPs, the number of employees is lacking, budget and infrastructure are adequate, program assistance is lacking in BUMDes management, but decision making is carried out by deliberation and in management there is a working relationship to achieve its goals in accordance with the organizational management that has been made. . Second, from the individual level the knowledge of the BUMDes management is inadequate, the lack of experience of the BUMDes management in increasing the success of the program makes the BUMDes management need to improve their skills, while in the work grouping there is a shared commitment to improving the success of the program, the behavior of the BUMDes management is fairly fast in providing services to the community and the enthusiasm of the community to change their welfare has become the motivation of the BUMDes management in increasing the success of the PK2 Jalin Matra program.